Potential Efficacy of Chitosan-Poly (Lactide-Co-Glycolide)-Encapsulated Trivalent Immersion Vaccine in Olive Flounder (Paralichthys olivaceus) Against Viral Hemorrhagic Septicemia Virus, Streptococcus parauberis Serotype I, and Miamiensis avidus (Scuticociliate) - Kole, Sajal; Dar, Showkat Ahmad; Shin, Su-Mi; Jeong, Hyeon-Jong; Jung, Sung-Ju (Frontiers in Immunology, 2021)
Olive flounder (Paralichthys olivaceus) is the most valuable aquaculture species in Korea, corresponding to 60% of its total production. However, infectious diseases often break out among farmed flounders, causing high mortality and substantial economic losses. Although some deleterious pathogens, such as Vibrio spp. and Streptococcus iniae, have been eradicated or contained over the years through vaccination and proper health management, the current disease status of Korean flounder shows that the viral hemorrhagic septicemia virus (VHSV), Streptococcus parauberis, and Miamiensis avidus are causing serious disease problem in recent years. Furthermore, these three pathogens have differing optimal temperature and can attack young fingerlings and mature fish throughout the year-round culture cycle. In this context, we developed a chitosan-poly(lactide-co-glycolide) (PLGA)-encapsulated trivalent vaccine containing formalin-killed VHSV, S. parauberis serotype-I, and M. avidus and administered it to olive flounder fingerlings by immersion route using a prime-boost strategy. At 35 days post-initial vaccination, three separate challenge experiments were conducted via intraperitoneal injection with the three targeted pathogens at their respective optimal temperature. The relative percentages of survival were 66.63%, 53.3%, and 66.75% in the group immunized against VHSV, S. parauberis serotype-I, and M. avidus, respectively, compared to the non-vaccinated challenge (NVC) control group. The immunized fish also demonstrated significantly (p < 0.05) higher specific antibody titers in serum and higher transcript levels of Ig genes in the mucosal and systemic tissues than those of NVC control fish. Furthermore, the study showed significant (p < 0.05) upregulation of various immune genes in the vaccinated fish, suggesting induction of strong protective immune response, ultimately leading to improved survival against the three pathogens. Thus, the formulated mucosal vaccine can be an effective prophylactic measure against VHS, streptococcosis, and scuticociliatosis diseases in olive flounder.